Investigation of Mechanical properties of Nitrided Weldments of Austenitic Stainless Steel After Quenching - Aminuddin, Ikhwan Syamim (IRC, 2016)
In this study the 316L austenitic stainless steel were tested with gas nitriding process. The time exposed for nitriding is fixed at 8 hours using Argon (30%) and Nitrogen (70%) gases with temperature at 400oC. The two separated sample piece welded together using Gas Tungsten Arc Welding (GTAW) and oil quenched. The sample undergo the nitriding process which will increase its mechanical properties. The presence of chromium carbide in the heat-affected zone (HAZ) due to welding temperature. From the experiment, the average hardness for un-nitrided and un-welded (UN + UW) sample have average of 393.52 HV while for un-nitrided and welded (UN + W) average of 460.66 HV and nitrided and welded (N + W) average of 661.84 HV. In addition, the ultimate tensile strength of un-nitrided and un-welded shows 572.36 MPa. The ultimate tensile strength of Un-Nitrided and Welded (UN + W) and Nitrided and Welded (N + W) sample was 369.694 MPa and 536.54 MPa respectively. In the presence of gas hardening process, the tensile strength showed higher value compared with un-nitride sample. In conclusion based on the hardness reading and tensile experiment, the mechanical strength of 316L increased by gas nitriding process.